DEKOLORISASI LIMBAH BATIK TULIS MENGGUNAKAN JAMUR INDIGENOUS HASIL ISOLASI PADA KONSENTRASI LIMBAH YANG BERBEDA - Ratna Stia Dewi; Sri Lestari (Molekul, 2010)
Azo as batik dyes are textile dyes which difficult to degradate. Fungus as bioremidiation organism are choosed to decolorize the dyes because its transformation ability, it can degradate toxic dyes component. The aim of research are to explore the fungus from Sokaraja-Banyumas batik industrial dyestuff, to know potential indigenous species wich can degradate it, to know dyestuff consentration which is degradated.Result of research showed that the isolation process of indigenous fungi from batik dyestuff in District Sokaraja Banyumas produce 4 isolates that have the potential dekolorization, they are 3 isolates of the genus Fusarium, and 1 isolate of the genus Aspergillus. That indigenous fungus can be used to decolorize dyestuff batik the decolorize percentage 69.346% -82.421%.